2019
DOI: 10.12688/gatesopenres.12979.2
|View full text |Cite
|
Sign up to set email alerts
|

The status of Ghanaian community health workers’ supervision and service delivery: descriptive analyses from the 2017 Performance Monitoring and Accountability 2020 survey

Abstract: Community-based services are a critical component of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…On this topic, the evidence is mixed. In a study from Ghana, the type of supervisor (i.e., community health officers, public health nurses, midwives, health assistants, and physician assistants) and type of facility (i.e., community health post, health centre, or hospital) to which the CHW was linked had no impact on the frequency of supervision, though the quality of supervision was not assessed [ 42 ]. Meanwhile, a qualitative study in South Africa concluded that supervision by senior nurses in facilities promoted better integration with the facility teams compared to supervision by a junior nurse [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…On this topic, the evidence is mixed. In a study from Ghana, the type of supervisor (i.e., community health officers, public health nurses, midwives, health assistants, and physician assistants) and type of facility (i.e., community health post, health centre, or hospital) to which the CHW was linked had no impact on the frequency of supervision, though the quality of supervision was not assessed [ 42 ]. Meanwhile, a qualitative study in South Africa concluded that supervision by senior nurses in facilities promoted better integration with the facility teams compared to supervision by a junior nurse [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18][19][20] In Ghana, for example, despite NCDs not being part of the formal programme, CHWs reported working on NCDs in nine out of 10 regions. 21 To date, there are very few examples of evaluations of polyvalent CHW programmes that incorporate multiple conditions in their care provision model. 3…”
Section: Key Questionsmentioning
confidence: 99%
“…In addition to varying definitions and framing of supervision, several studies have noted challenges with how it is implemented. Not only is there a lack of evidence on what 'good supervision' for CHWs entails (Assegaai & Schneider, 2019), but there is also variability in supervisory interactions across different geographical contexts and programmes, resulting in a lack of consistency or development of best practices (Schwarz et al, 2019). As a result, there is a need for studies to explore how supervision for CHWs is positioned, its purpose and ways to support effective delivery (Agarwal et al, 2019;Nkomazana et al, 2016).…”
Section: Introductionmentioning
confidence: 99%